Viabilidade econômica para implantação de cultivo de eucalipto para fins energéticos na Seara Indústria e Comercio de Produtos Agropecuários Ltda. - Goltz, Victor (2012)
The investment in reforestation with Eucalyptus as a way to ensure the cheap and quality supply of plant biomass to be used as an energy source in grain dryers, is constantly put into evidence in cereal companies and agricultural cooperatives. Like any other economic activity, needs to be assessed from the point of view of their financial return on invested capital, so that it can contribute to support the decisions. Thus, this study aims to analyze the economic feasibility for implementation of reforestation with eucalyptus to supply the needs of firewood in Seara Industria e Comercio de Produtos Agropecuarios Ltda in its three receiving, processing and storage plants installed in northern Parana. The calculation methodology took into consideration the needs of firewood annual production costs during the production cycle of 21 years , with cuts every 7 years, and considering that the price of wood is the one practiced by the regional market. To analyze the feasibility, we considered the assessment criteria for Net Present Value (NPV) and Internal Rate of Return (IRR) in two scenarios: a) considering the purchase area, b) considering the lease area. Both alternatives took into account areas far more than 150 km of consumer units. The opportunity cost considered was 6.0% per year. It was concluded that, investment in forestry as a source of biomass for energy, are economically feasible and provided the lease area required, being economically unfeasible scenario in purchasing the required area.